Property rights, risk, and livestock development in Africa - McCarthy, Nancy; Swallow, Brent M.; Kirk, Michael; Hazell, Peter B. R. (International Food Policy Research Institute, 1999)
In 1996, the International Livestock Research Institute (ILRI), the International Food Policy Research Institute (IFPRI), and the Institute for Rural Development at the University of Goettingen began a research project aimed at providing in -formation to improve the efficiency, equity, and environmental sustainability of livestock production and land use in Sub-Saharan Africa. The project focused on semi-arid areas where mobile livestock-production and mixed crop–livestock production are competing land uses. It is estimated that a population of 87 million live in these areas, and these people are among the poorest in the world. Not only are average incomes low, but their livelihoods are also subject to a great deal of risk—environmental, tenurial, social, and political.